Development of a Clinician-Administered National Institutes of Health-Brief Fatigue Inventory: a Measure of Fatigue in the Context of Depressive Disorders - Saligan, Leorey N. (J Psychiatr Res, 2015)
OBJECTIVE: Fatigue is a complex, multidimensional condition. Although it is often associated with depression, it is not known whether it has a distinct network from depression or whether it can be clinically evaluated, separately. This study describes preliminary findings in the development of a brief, clinician-administered instrument to measure fatigue in the context of depressive disorders using items from existing clinician-administered depression and mania scales. METHODS: Based on items from prior fatigue measurements, items were selected from the Hamilton Depression Rating Scale (HDRS), Montgomery-Asberg Depression Rating Scale (MADRS), Young Mania Rating Scale, and Structured Interview Guide for HDRS with Atypical Depression. The final items composed the NIH-Brief Fatigue Inventory (NIH-BFI). Responses from 89 depressed adults collected pre- and post-antidepressant therapy (ADT) determined the reliability and consistency of the NIH-BFI using Cronbach’s alpha and principal components analysis (PCA). Correlations of the NIH-BFI and fatigue items from other scales before and after ADT explored validity. RESULTS: The 7-item NIH-BFI had Cronbach alphas ranging from 0.81–0.88 and PCA indicating a single dimension. The NIH-BFI score was strongly correlated (r=0.73, p<0.001) with fatigue items from Beck Depression Index, with MADRS without fatigue items (r=0.77, p<0.001), and HDRS without fatigue items (pre: r=0.69, p<0.001). CONCLUSIONS: Preliminary findings show support for internal consistency reliability and validity of the NIH-BFI, a clinician-administered measure of fatigue. Further testing in other clinical populations is recommended to obtain additional information on reliability and validity. The NIH-BFI provides a method for clinician-rated fatigue that may be a separate from depression.